Peran Guru Pendamping Khusus Dalam Meningkatkan Kreativitas Dan Kemandirian Peserta Didik Abk Melalui Sensory Fest Kelas I Di Sd Muhammadiyah 2 Sidoarjo - Adillatul Aizzah (AL-THIFL : Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to describe the role of Special Assistant Teachers (GPK) in increasing the creativity and independence of students of Children with Special Needs (ABK) through Sensory Fest activities at SD Muhammadiyah 2 Sidoarjo. This study uses a qualitative approach with a descriptive type of research. The subjects in this study include GPK, classroom teachers, ABK students, and parents. Data is collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawn. The results of the study show that GPK plays an active role in all stages of Sensory Fest activities, starting from planning, implementation, to evaluation. This activity has a positive impact on the development of creativity and independence of ABK students, such as increasing children's ability to complete independent tasks and the emergence of creative expression in various sensory activities. However, several challenges were found, such as changes in the mood of ABK students. This study concludes that Sensory Fest is an effective and relevant learning strategy in inclusive education, with GPK as a key actor in assisting the development of ABK students. Keywords: Special Education Teacher; students with special needs; creativity; independence; sensory fest